Segmentation of cluster organization in business subject (BS) - Beknazarova Manzura Bakhtiy orovna (THE INNOVATION ECONOMY, 2026)
This article highlights the importance of interregional clustering of economic entities in the effective con duct of market relations, and subjectively approaches the development of the principle and conceptual framework for taking into account the natural resources, infrastructure and demographic situation of the region in the organiza tion of clusters and developing normative documents adopted on a nationwide scale in accordance with the region.